Copypastas: o primado da forma e a regra do caos – uma análise de discurso digital - Stefani, Helena Bonuccelli (Universidade Federal de São Carlos, 2024)
In this Final Paper, based on the theory of Materialist Discourse Analysis and Digital Discourse Analysis, I try to identify, explain and describe the discursive functioning of the so-called copypastas. As an object, copypastas – a technogenre (Paveau, 2021) – are ‘‘blocks of text'' which, through the action of copying and pasting (and therefore ''copy''/''pasta''), circulate and crystallize in digital environments through spam. Generally ironic, their signification and production of sense – considering the gestures of interpretation of user-subjects – are necessarily linked to the fact that this block of text is identified as a copypasta. In order to understand its discursive functioning, I analyze “prototypical” excerpts, considering the instances of production of sense, namely: constitution, formulation and circulation, according to Orlandi (2022). I then analyze the way in which the “birth” of non-prototypical copypastas take place – and the obstacles to their “survival”. Based on these analyses, I propose the “hypothesis” of the meta-existence of copypastas: through a hyperbole, they would be indicative of the basic functioning of discourses of/in the digital world. The “rule” in the chaos of online discursive production is the “primacy of form” - that is, the thought that the “physical form” of a text overdetermines its meaning, due to the co-enunciative weight that the technical (including the algorithmic, the “behind the screen”) brings to digital discourses.
Copypastas: the primacy of form and the rule of chaos – a digital discourse analysis
Keywords: Copypasta; Tecnogênero; Análise do discurso digital; Digitalidade; Interpretação; Technogenre; Digital discourse analysis; Digitality; Interpretation; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA